(untitled) (Bangladesh Journal of Nuclear Medicine, 2021)
Follicular carcinoma of thyroid usually behaves in an indolent manner with low metastatic potential. Distant metastases as initial presentation are rare in follicular carcinoma, especially in young patients. Blood borne metastasis is common with spread to lung, bone and other solid organs. However, metastatic mediastinal tumors are rare. Here, a neglected case of follicular carcinoma of thyroid (FTC) is reported. The patient is a 43 year old female who was referred to the Thyroid Division of NINMAS for radioiodine therapy for an inoperable metastatic FTC. She was presented with fever, shortness of breath and chest discomfort. 99mTc scan showed concentration of most of the isotope in the big metastatic mediastinal mass. Because of the sheer volume of the mass, a plan was undertaken to first reduce her tumor burden with external beam radiation therapy (EBRT) and then considered adjuvant therapy with radioiodine after manageable regression in size of the metastatic tumor. She had a history of thyroidectomy for FTC 14years back without radio iodine ablation. Negligence about proper management for FTC may result in poor outcome like huge mediastinal mass as in this reported case. Radioiodine therapy is usually the first line approach for functional metastasis, but in exceptional cases when the tumor size is very big, EBRT may be considered first. Radiotherapy (RT) is effective in relieving compression symptoms and may improve the quality of life in these patients. Bangladesh J. Nuclear Med. 22(2): 141-145, Jul 2019